Analisis Pertanggungjawaban Asuransi terhadap Kegagalan Pembayaran oleh Perusahaan Asuransi Jiwa - Didit Firmansyah; Eldrida Joan Karnois; Sindi Susanti; Syalsa Nabila Anisa (Letterlijk, 2025)
The growth of the life insurance industry has increased significantly in the last two decades, in line with the increase in financial literacy and corporate and public awareness of the importance of protecting the things they own. The content of the insurance agreement is to transfer losses due to unexpected events suffered by the insured to the insurer and the insured must pay premiums to the insurer. The purpose of this study is to determine how the insurance company is responsible if there is a failure to pay. The methodology used by the author is normative legal methodology. Normative research or library legal research is legal research using secondary data, namely data obtained from library materials. The results of the study show that if there is a failure to pay by the insurance company and internal efforts are unsuccessful, the policyholder can report the case to the LAPS SJK. The role of the Financial Services Authority (OJK) is very vital in supervising and taking action against insurance companies that fail to fulfill their obligations. OJK can impose administrative sanctions up to revoking business licenses, as happened in the case of Wanaartha Life. Cases like this show the importance of implementing Good Corporate Governance (GCG) and strict risk management by insurance companies, as well as the need to strengthen the consumer protection system so that similar incidents do not continue to recur.